Development of Imagination Play Media in Listening to Poetry Learning - Wicaksono, Helmi; Muttaqin, Khoirul; Lailiyah, Fithrotul (EDUCATIO : Journal of Education, 2023)
Learning media is one of the supporting factors so that learning objectives can be achieved. Imagination game media in learning to listen to poetry is one of learning to listen to poetry by utilizing poetry reading videos, poetry musicalization, and poetry dramatization which can stimulate imagination. Imagination game media is also accompanied by a guidebook for teaching listening and student worksheets called LKM (Listening Worksheet). The research model used in this development research is the Borg & Gall procedural model which is then adapted to the needs and conditions of the research. The test results of this imagination game media product discuss the analysis of the test results on (4.2.1.) product attractiveness and (4.2.2.) product effectiveness. In the aspect of the attractiveness of the media appearance, a score of 75% was obtained, the attractiveness of the content received a score of 75%, and the attractiveness of the language received a score of 75%. As for the aspect of media effectiveness with the theory of listening to poetry, a score of 75%, the effectiveness of the media with the needs of high school students gets a score of 75%, and the accuracy of the media in guiding the achievement of learning objectives of listening to poetry gets a score of 75%. That is, according to the data above it shows that the aspects of the attractiveness and effectiveness of imaginative game media products are feasible to be implemented in learning to listen to poetry.